2017
DOI: 10.1158/1535-7163.mct-17-0114
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of the p90RSK–CDC25C Pathway Leads to Bypass of the Ganetespib-Induced G2–M Arrest and Mediates Acquired Resistance to Ganetespib inKRAS-Mutant NSCLC

Abstract: A subset of non-small cell lung cancers (NSCLC) are dependent upon oncogenic driver mutations including the most frequently observed driver mutant KRAS which is associated with a poor prognosis. As direct RAS targeting in the clinic has been unsuccessful to date, use of Heat shock protein 90 (Hsp90) inhibitors appeared to be a promising therapy for KRAS mutant NSCLC, however limited clinical efficacy was observed due to rapid resistance. Furthermore, the combination of the Hsp90 inhibitor (Hsp90i), ganetespib … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 53 publications
2
15
0
Order By: Relevance
“…Recent preclinical research in our laboratory has led to the discovery of the ganetespib resistance mechanism in KRAS mutant NSCLCs. We have not only demonstrated that the acquired resistance to ganetespib in KRAS mutant NSCLC is due to the hyperactivation of critical ERK1/2-p90RSK-mTOR signaling arc and subsequent bypass of G 2 -M checkpoint arrest [ 274 , 275 ]. Moreover, we observed that ganetespib resistance led to cross resistance to the anti-microtubule agent, docetaxel, which could explain the failure of the Galaxy-2 trial [ 274 ].…”
Section: Hsps and Their Role As Molecular Chaperones In Aiding Malmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent preclinical research in our laboratory has led to the discovery of the ganetespib resistance mechanism in KRAS mutant NSCLCs. We have not only demonstrated that the acquired resistance to ganetespib in KRAS mutant NSCLC is due to the hyperactivation of critical ERK1/2-p90RSK-mTOR signaling arc and subsequent bypass of G 2 -M checkpoint arrest [ 274 , 275 ]. Moreover, we observed that ganetespib resistance led to cross resistance to the anti-microtubule agent, docetaxel, which could explain the failure of the Galaxy-2 trial [ 274 ].…”
Section: Hsps and Their Role As Molecular Chaperones In Aiding Malmentioning
confidence: 99%
“…We have not only demonstrated that the acquired resistance to ganetespib in KRAS mutant NSCLC is due to the hyperactivation of critical ERK1/2-p90RSK-mTOR signaling arc and subsequent bypass of G 2 -M checkpoint arrest [ 274 , 275 ]. Moreover, we observed that ganetespib resistance led to cross resistance to the anti-microtubule agent, docetaxel, which could explain the failure of the Galaxy-2 trial [ 274 ]. Although the failure of the Galaxy-2 trial led to cessation of any preclinical or clinical development of ganetespib, our preclinical analyses strongly suggest that the combination of ganetespib with an ERK1/2 inhibitor, or a p90RSK inhibitor or a CDC25C inhibitor would be an efficacious therapeutic strategy to test in the clinic [ 274 ].…”
Section: Hsps and Their Role As Molecular Chaperones In Aiding Malmentioning
confidence: 99%
See 1 more Smart Citation
“…HSP90, an upstream factor known to induce ERK/MAPK activation, and RPS6KA1, a downstream target of the ERK/MAPK signaling cascade, have been identified as therapeutically targetable. 35,36 There is also a reduction in the expression levels of well-established oncogenes, such as TGFBR3, FGFR2, FGFR4, LGR4, LGR5, PDGFRA, PDK3, SOX2, TCF19, E2F8, and MYB, by doxycycline (Table S2, online only). When comparing the genes downregulated by doxycycline with (1) those downregulated by PD98059 (data not shown) and (2) the gene set representing the ERK/MAPK pathway, we identified considerable overlap (Table S6, online only).…”
Section: Functional Genomic Investigation Of the Genes That Were Idmentioning
confidence: 99%
“…S6C; refs. 42,43). A common feature of cellular transformation is loss of cilia (10); for compounds causing increased ciliation, we also investigated whether they possessed similar activities in transformed cancer cells, as well as immortalized but nontransformed models.…”
Section: Detailed Analysis Of the Action Of Sunitinib Erlotinib Andmentioning
confidence: 99%